2022
DOI: 10.1007/s10592-022-01468-0
|View full text |Cite
|
Sign up to set email alerts
|

A range-wide analysis of population structure and genomic variation within the critically endangered spiny daisy (Acanthocladium dockeri)

Abstract: Understanding population structure and genetic diversity is important for designing effective conservation strategies. As a critically endangered shrub, the six remaining extant populations of spiny daisy (Acanthocladium dockeri) are restricted to country roadsides in the mid-north of South Australia, where the species faces many ongoing abiotic and biotic threats to survival. Currently the spiny daisy is managed by selecting individuals from the extant populations and translocating them to establish insurance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 90 publications
(105 reference statements)
0
0
0
Order By: Relevance
“…Indeed, recent studies have now demonstrated that allozymes provide exceptional concordance with a companion SNP dataset for the delineation of all primary and admixed lineages in every group examined thus far (Gadopsis, Unmack et al 2017;Hypseleotris, Unmack et al 2019;Retropinna, Unmack et al 2022; Craterocephalus, Mogurnda and Rhadinocentrus, M. Adams and P. J. Unmack, unpubl. data), and can even provide comparable insights into fine-scale population structure (Jusaitis and Adams 2005;Brooks et al 2022).…”
Section: Combined Allozyme Analysis Of G Truttaceus Species Groupmentioning
confidence: 99%
“…Indeed, recent studies have now demonstrated that allozymes provide exceptional concordance with a companion SNP dataset for the delineation of all primary and admixed lineages in every group examined thus far (Gadopsis, Unmack et al 2017;Hypseleotris, Unmack et al 2019;Retropinna, Unmack et al 2022; Craterocephalus, Mogurnda and Rhadinocentrus, M. Adams and P. J. Unmack, unpubl. data), and can even provide comparable insights into fine-scale population structure (Jusaitis and Adams 2005;Brooks et al 2022).…”
Section: Combined Allozyme Analysis Of G Truttaceus Species Groupmentioning
confidence: 99%